2022
DOI: 10.21203/rs.3.rs-2121605/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Demographic characteristics and risk factors related to high blood pressure among healthy blood donors from Luanda, Angola

Abstract: Hypertension is a public health concern, mainly in resource-limited countries. We investigated the characteristics and risk factors related to high blood pressure in healthy blood donors from Angola. This was a multicentre retrospective study that includes 343 donors from December 2019 to September 2020. Men represented 93% of the population. The mean age was 32 ± 9 years. Mean systolic blood pressure (SBP) was 131 ± 12.3mmHg (ranging from 100mmHg to 160mmHg) and diastolic blood pressure (DBP) was 80.1 ± 9.72m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
3
1
Order By: Relevance
“…The data found in the present study showed that hypertension was prevalent in most of the population studied, with about 67% affected by high blood pressure. The prevalence of high blood pressure in the present study was higher than that reported by Sebastião, et al [7][8][9][10] in a study addressing the Demographic characteristics and risk factors related to high blood pressure among healthy blood donors from Luanda, the capital city of Angola, where about 7.3% of the population had high blood pressure (>140/90 mmHg) [10].…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…The data found in the present study showed that hypertension was prevalent in most of the population studied, with about 67% affected by high blood pressure. The prevalence of high blood pressure in the present study was higher than that reported by Sebastião, et al [7][8][9][10] in a study addressing the Demographic characteristics and risk factors related to high blood pressure among healthy blood donors from Luanda, the capital city of Angola, where about 7.3% of the population had high blood pressure (>140/90 mmHg) [10].…”
Section: Discussioncontrasting
confidence: 73%
“…Studies carried out in Angola on hypertension and associated risk factors, specifically in Bengo, Huambo, Luanda and Lubango, revealed a significant prevalence of hypertension among the young population and a low level of knowledge about this cardiovascular disease [7][8][9][10]. Despite that, there are few studies published on the prevalence and risk factors of hypertension in Angola, particularly in Huambo, one of the provinces, located in the centre of the country.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of high blood pressure in the present study was higher than that reported by Sebastião et al in a study addressing the Demographic characteristics and risk factors related to high blood pressure among healthy blood donors from Luanda, the capital city of Angola, where about 7.3% of the population had high blood pressure (>140/90 mmHg). [10] In an epidemiological cohort study conducted among individuals from Poland, Zatonska et al (2023) found that several factors played a significant role in increasing the chances of developing hypertension after nine years. These factors included gender, educational level, body weight, alcohol consumption, and embracing a healthy lifestyle.…”
Section: Discussionmentioning
confidence: 99%
“…[6] Studies carried out in Angola on hypertension and associated risk factors, specifically in Bengo, Huambo, Luanda and Lubango, revealed a significant prevalence of hypertension among the young population and a low level of knowledge about this cardiovascular disease. [7][8][9][10] Despite that, there are few studies published on the prevalence and risk factors of hypertension in Angola, particularly in Huambo, one of the provinces, located in the centre of the country. Therefore, the present study aimed to investigate the prevalence and factors associated with hypertension in Huambo, in order to contribute to the definition of strategies for controlling cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%